2020
DOI: 10.1021/acssuschemeng.0c05637
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Kinetic Control Aspects to Explain the Performances and Elucidate the Mechanisms of Oriented Membrane Processes for Extraction and Recovery of Glycerol Compound

Abstract: Facilitated extraction membrane processes present a promising technology to replace conventional methods of producing and purifying glycerol. They offer green, ecofriendly, and sustainable platforms with economic benefits. Therefore, in this article, we are interested in improvements to current glycerol purification techniques, in particular, the development of a more efficient, cost-effective, and sustainable glycerol purification process. The current work presents studies relating to the use of three polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(61 reference statements)
2
4
0
Order By: Relevance
“…The increase in the WV diffusion flux with temperature (Figure ) and the low activation energy E a (<50 kJ mol –1 ) indicate that the reaction between the WV molecule and the interaction site of the IL agent is a simple reaction (association/dissociation) by formation and decomposition of an unstable intermediate entity (WV-IL) ≠ (Figure S3), which orients and ensures better water vapor diffusion. Previous studies, carried out within our laboratory ,, confirm the described results and indicate that the molecules of water vapor move by a mechanism of jumps on the charged and oriented sites of the ionic liquid agents.…”
Section: Resultssupporting
confidence: 86%
“…The increase in the WV diffusion flux with temperature (Figure ) and the low activation energy E a (<50 kJ mol –1 ) indicate that the reaction between the WV molecule and the interaction site of the IL agent is a simple reaction (association/dissociation) by formation and decomposition of an unstable intermediate entity (WV-IL) ≠ (Figure S3), which orients and ensures better water vapor diffusion. Previous studies, carried out within our laboratory ,, confirm the described results and indicate that the molecules of water vapor move by a mechanism of jumps on the charged and oriented sites of the ionic liquid agents.…”
Section: Resultssupporting
confidence: 86%
“…The feed phase consists of the paracetamol substrate solution, while the receiving phase consists of distilled water (with or without activated carbon). In order to maintain the same temperature during the studied processes, the system was immersed in a thermostatic water bath …”
Section: Methodsmentioning
confidence: 99%
“…In order to maintain the same temperature during the studied processes, the system was immersed in a thermostatic water bath. 37 Paracetamol was purchased from ICN Biomedicals, and its concentration was taken from the source phase every hour. The analysis was conducted at the maximum absorption wavelength (λ max = 243.40 nm) using a UV−vis spectrometer (UV/VIS Excellence, Mettler Toledo) in the wavelength range of 190−1100 nm.…”
Section: Methodsmentioning
confidence: 99%
“…70 This interpretation is also confirmed and consolidated by the work of some members of M. Hlaibi's team on the diffusion processes of different substrates, organic molecules and ions. 93…”
Section: Capillary Flow Porometermentioning
confidence: 99%
“…Various studies on diffusion processes of substrates through PIMs have suggested the formation of unstable intermediate entities [H 2 O-IL] # through the interaction between substrate molecules (H 2 O) and extractive agent sites (ILs). 93,[96][97][98][99] The data in Table 4 indicate that the incorporation of the TBAPF 6 IL agent in the membrane phase favored the diffusion of water vapor. Analysis of previous results revealed low values for activation energies (E a and ΔH ≠ ), confirming the observed performances of the developed membranes.…”
Section: Mechanism Of Water Vapor Diffusion Through the Membranementioning
confidence: 99%